The Latent Structure of Negative Symptoms in Individuals With Attenuated Psychosis Syndrome and Early Psychosis: Support for the 5 Consensus Domains. (10th September 2020) - Chang, Wing Chung; Strauss, Gregory P; Ahmed, Anthony O; Wong, Sandra C Y; Chan, Joe K N; Lee, Edwin H M; Chan, Sherry K W; Hui, Christy L M; James, Sydney H; Chapman, Hannah C; Chen, Eric Y H
Abstract: Negative symptoms are prevalent in the prodromal and first-episode phases of psychosis and highly predictive of poor clinical outcomes (eg, liability for conversion and functioning). However, the latent structure of negative symptoms is unclear in the early phases of illness. Determining the latent structure of negative symptoms in early psychosis (EP) is of critical importance for early identification, prevention, and treatment efforts. In the current study, confirmatory factor analysis was used to evaluate latent structure in relation to 4 theoretically derived models: 1. a 1-factor model, 2. a 2-factor model with expression (EXP) and motivation and pleasure (MAP) factors, 3. a 5-factor model with separate factors for the 5 National Institute of Mental Health (NIMH) consensus development conference domains (blunted affect, alogia, anhedonia, avolition, and asociality), and 4. a hierarchical model with 2 second-order factors reflecting EXP and MAP, as well as 5 first-order factors reflecting the 5 consensus domains. Participants included 164 individuals at clinical high risk (CHR) who met the criteria for a prodromal syndrome and 377 EP patients who were rated on the Brief Negative Symptom Scale. Results indicated that the 1- and 2-factor models provided poor fit for the data. The 5-factor and hierarchical models provided excellent fit, with the 5-factor model outperforming the hierarchical model. These findings suggest that similar to the chronic phase of schizophrenia, the latent structure of negative symptom is best conceptualized in relation to the 5 consensus domains in the CHR and EP populations. Implications for early identification, prevention, and treatment are discussed.